Hubungan Umur Kehamilan dan Paritas dengan Kejadian Anemia dada Ibu Hamil - Fauzul Munah; Dinar Indri Bakti Salsabila (Jurnal Impresi Indonesia, 2025)
Anemia during pregnancy is a health problem that affects almost half of all pregnant women worldwide. One of the influencing factors is gestational age and parity. The purpose of this study was to determine the relationship between gestational age and parity with the incidence of anemia in pregnant women. This type of research is analytical research with a cross-sectional design, using the Chi-square test. In this study, observation sheets were provided and conducted once. The sampling technique in this study used a purposive sampling technique. The sample in this study were 32 pregnant women in the third trimester. Respondents in this study were pregnant women in the third trimester at BPM L Bogor Regency. The study was conducted in July 2025. Statistical tests in this study used the chi-square test. The results of this study indicate a relationship between gestational age (p-value = 0.000), parity (p-value = 0.000) with the incidence of anemia in pregnant women. It is hoped that this study can provide knowledge for pregnant women so that they can improve the quality of maternal and fetal health.